PENGARUH BATU CADAS (BATU TRASS) SEBAGAI BAHAN PEMBENTUK BETON TERHADAP KUAT TEKAN BETON - Herdiansyah Herdiansyah; Mekar Ria Pangaribuan (Inersia: Jurnal Teknik Sipil, 2019)
The concrete is material construction it’s substantial cement Portland and agregat is sand and stone (split). Usually, concrete use for house construction, building, bridge and street. The agregat is important material volume in concrete mixture. Quality of concrete is found from planning and monitoring more better through material in use, like truss stone. It is change of  material from split stone, with purpose get the influence truss strong pressure concrete and tofound the point of maximum strong pressure concrete can it get. This research do in the labaoratorium building trial conctruction field and building, publick woker official, Bengkulu goverment use 36 test. They are material test with normal concrete, material test use 25% experiment truss stone and material test 50% truss stone what coarse agregat. Appraisal data final trial is c0llection, it's processing and make it become a report. Trial strong pressure concrete begin with design article test (mix design) and trial strong pressure concrete at 7 days, 14 days, 21 days and 28 days. Appraisal data final are process with simple regresi linier method. The end, this result of research is strong pressure concrete get with 25% truss stone is 164,73 kg/cm2, and use 50% truss stone us 106,94 cm/kg2. This result show very far away from plan strong prsessure concrete, it is suggestion that’s concrete use for floor.